2010
DOI: 10.1524/zkri.2010.1214
|View full text |Cite
|
Sign up to set email alerts
|

Simple method for preparing monoclinic single crystals of zeolite ZSM-5 and analysis of their structure

Abstract: A simple method for preparing monoclinic single crystals of ZSM-5 is developed. The ZSM-5 crystals are pressed with a weight of 50 g at an angle of 45° relative to the b and c crystallographic axes of twin ZSM-5 crystals while the temperature is simultaneously increased to 573 K. The temperature is then slowly reduced to 313 K, and these steps are repeated three times. The monoclinic structure of the single crystals of ZSM-5 prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…The authors assumed that these single crystals were orthorhombic by analogy with the preparation of simple monoclinic silicalite-1 (Kamiya et al, 2010). The authors confirmed that they were orthorhombic according to the results of the structure analysis of orthorhombic benzenesilicalite-1.…”
Section: Figurementioning
confidence: 85%
See 4 more Smart Citations
“…The authors assumed that these single crystals were orthorhombic by analogy with the preparation of simple monoclinic silicalite-1 (Kamiya et al, 2010). The authors confirmed that they were orthorhombic according to the results of the structure analysis of orthorhombic benzenesilicalite-1.…”
Section: Figurementioning
confidence: 85%
“…Normally calcination of the crystals to remove TPA ions results in cracking over 80% of the crystals (Geus & van Bekkum, 1995). A sodium perchlorate treatment was developed by the authors to avoid crystal cracking (Kamiya et al, 2010). After this treatment, the crystals were calcined at 763 K in flowing air for 1 h to obtain monoclinic twin silicalite-1 crystals.…”
Section: Sodium Perchlorate Treatment and Calcinationmentioning
confidence: 99%
See 3 more Smart Citations